Use of Single Cell Transcriptomic Techniques to Study the Role of High-Risk Human Papillomavirus Infection in Cervical Cancer - Meng, Lingzhang; Chen, Shengcai; Shi, Guiling; He, Siyuan; Wang, Zechen; Shen, Jiajia; Wang, Jiajia; Sooranna, Suren Rao; Zhao, Jingjie; Song, Jian (Frontiers in Immunology, 2022)
High-risk human papillomavirus (hrHPV) infection has been associated with a higher probability of progression to cervical cancer. However, several extensive studies have reported that the presence of hrHPV can lead to a better prognosis, but the mechanism of how this occurs is unclear. In this study, microbiological analysis was used to identify HPV as a favourable virus for the prognosis of patients with cervical squamous cell carcinoma (CSCC). Using single-cell RNA-sequencing (scRNA) data and viral tracking methods to identify HPV+ and HPV- malignant cells, we compared the interactions of HPV+ and HPV- malignant cells with immune cells as well as the trajectory of malignant cells with or without HPV. Combining the scRNA and TCGA bulk-seq data, we identified a set of unfavourable molecules, including ITGB1, CXCR1, VEGFA and TNFR10B/DR5, which is upregulated in the HPV- CSCC cells. This study provides a basis for the development of a rational post-operative follow-up programme and the development of an appropriate treatment plan for patients with cervical cancer.